Proposed laboratory surrogate markers for the management of acute kidney injury in ethylene glycol poisoning in resource-challenged countries; a Mayo Clinic Health System, Wisconsin, case analysis - Macaulay Amechi Onuigbo; Eileen Samuel; Nneoma Agbasi; Adel Zurob (Society of Diabetic Nephropathy Prevention, 2018)
Mass poisonings with diethylene glycol (DEG) usually ingested as an unintended component of pharmaceutical preparations have occurred in Nigeria, especially affecting children with nearly 100% mortality outcomes. Clearly, the unavailability of Specialty Toxicology laboratory testing facilities translates to non-diagnosis and therefore inappropriate management of these patients with resulting poor outcomes. In this case analysis, while utilizing a case report involving intentional DEG intoxication that we managed at the Mayo Clinic Health System in North-Western Wisconsin, we have demonstrated the utility of serial values of commonly available blood test parameters including serum bicarbonate and anion gap, blood ABG pH and CO2 values, together with the use of serum osmolality gap as surrogates to expedite early and appropriate treatment of such cases even in the absence of Toxicology confirmation of DEG as the poisoning agent. Based on the experience gained from this case report, we strongly recommend that the responsible governments in resource-challenged countries must ensure that these laboratory surrogate indices, at the minimum, become available in the hospitals. This would improve outcomes in general.